Concept development of an interactive terminal for clothing stores - Ekersund, Evelina (2012)
This master’s thesis has been written as part of the Master Programme in Industrial Design Engineering at Luleå University of Technology and was conducted for The Interactive Institute, at Sonic Studio in Piteå. The Interactive Institute is an experimental IT & design research institute and Sonic Studio is one of its organizational groups. The assignment was to design a terminal that would provide the target market with a marketing tool and its customers with information about the store’s assortment.Clothing stores were chosen as the target market for the project, since that idea seemed to have the most potential. To get an overview of the current situation, information about user needs and wishes were gathered through a web questionnaire for clothing store customers and interviews with store managers. Almost all of the participants in the web questioner preferred shopping for clothes in a store, but many described problems with the order of the garments and the size labeling. The interviews with the store managers showed many similarities between the stores, regarding the sorting and locating of clothes. The customer’s situation was further explored by creating a storyboard and describing “best case scenarios”. Demands and wishes were documented in a requirement specification. A benchmarking study was conducted by searching the Internet. This study showed that many different products have been made to contribute to a better shopping experience for the customers, such as interactive mirrors, scanning devises and body scans. The focus of the products is on information, assistance, interaction, flexibility and efficiency. Two sketchy interfaces were created, one for the terminal and one for a smartphone application. The sketches have been made with the intent to provide as much information as possible but at the same time limit the information shown at one time. The interface for the terminal has an intro movie with an animation and a melody that is meant to catch the customers’ attention. The other sounds, ...